Development of a radio unit for a 5G C-RAN testbed - Renca, Filipe Miguel Diogo (2022)
The arrival of 5G brings telecommunications engineers a set of challenges to solve. This new generation of mobile communications brings faster speeds, higher bandwidth, lower latency and superior quality of service when compared with 4G/LTE. This dissertation studies the update of the ORCIP testbed using analogue radio-over-fibre (RoF) transmission. For that, a study and characterisation of an optical link using a TOSA and a ROSA are made to replace the current structure based on low-cost SFP transceivers. A remote radio unit is developed containing a radio frequency frontend and the developed analogue optical link. This radio frequency frontend is designed for the N78 band of 5G FR1 in Portugal. The performance of the developed frontend is analysed in conjunction with the optical link using an actual 5G signal.